"The Final Word"?: The Qurʾan and Karl Rahner in Dialogue. (9th June 2016) - Perkins, Tasi
Abstract : Muslim-Christian conversation has historically broken down over three Qur'anic objections to Christian doctrine. The Trinity, the Incarnation, and the Crucifixion all seem to be repudiated in Islamic scripture. Karl Rahner, one of the Catholic scholars who drove Vatican II's theological agenda, did not comment much on Islam, so putting him in dialogue with a tradition about which he was relatively uniformed might initially seem strange. Nevertheless, and perhaps because of his distance from Islam, his thought might allow fresh angles with which to approach these core difficulties. In particular, his concept of divine modalities—which for him render Christianity "radically" monotheistic—makes him a useful dialogue partner for Islam, one of whose primary tenants is that God is one and not three. His focus on Logos theology gives him an inroad to the Qur'anic explanation of Christ as "the word of God." Finally, his "theology from below" allows for an experiential rather than metaphysical understanding of God's presence amongst humanity. This paper offers a Rahnerian grounding from which to approach the doctrine of God in Muslim-Christian dialogue.